Correlation between spirituality, religiosity and quality of life of adolescents - Farinha, Francely Tineli (2018)
This study consists in an integrative review of the literature, conducted through electronic search in Lilacs, PubMed, Scopus and Web of Science databases. Articles published in the last five years (2012-2017), were selected, primary, available in full, in English, Portuguese or Spanish. The following descriptors were used: Spirituality, religion, quality of life and adolescence, which have been combined with their respective synonyms. A total of 10 articles were included, from which three thematic categories emerged: 1) Favoring and strengthening spirituality and/or religiosity in adolescents; 2) Repercussions of spirituality and/or religiosity referring to the situational confrontation; and 3) Influence of spirituality and/or religiosity in the quality of life of adolescents. There was consensus among the authors studied that there is a strong correlation between religiosity and / or spirituality in the quality of life of adolescents.